عصر حاضر میں مردو زن کامخلوط معاشرتی نظام اور اس کے نتائج وثمرات ؛قرآن و سنت کی روشنی میں تحقیقی جائزہ: The Consequences and Results of Promiscuous Society in the Contemporary era A Research Review in the light of Qur’ān & Sunnah - Mubashir, Asadullah; Barkati, Muhammad Kashif (Al-Amīr Research Journal for Islamic Studies, 2023)
This article delves into the complexities and consequences of a Promiscuous Society, where men and women coexist and interact within various societal structures. It delves into the theological, social, and psychological ramifications of interactions between genders in various contexts, considering both the benefits and challenges inherent in such arrangements. Drawing from Islamic scripture and prophetic traditions, the article offers insights into the importance of modesty, respect, and boundaries in fostering healthy and harmonious social dynamics between men and women. Furthermore, it explores the potential consequences of deviating from these principles, emphasizing the need for adhering to divine guidance in navigating contemporary societal norms. Through a comprehensive analysis grounded in Islamic principles, this article seeks to contribute to a nuanced understanding of gender interactions in the modern world while upholding the timeless wisdom of Quranic teachings and the Sunnah. Key Words: Promiscuous Society, Gender equality, Interaction, Co-education.